2015
DOI: 10.5152/anatoljcardiol.2015.6326
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nigella sativa L. seed oil on intima–media thickness and Bax and Caspase 3 expression in diabetic rat aorta

Abstract: Objective:Hyperglycaemia is an important risk factor for the development and progression of the macrovascular and microvascular complications that occur in diabetes. The expression of apoptotic markers in the aortic medial layer of diabetic rats and the effects of N. sativa L. seed oil on the expression of these markers were investigated in this study.Methods:Four-month-old adult female Wistar rats (n=21) were divided into 3 groups: Group 1, control; Group 2, diabetes and Group 3, diabetes+N. sativa L. seed oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…NS significantly increases the expression BCL2 in cardiac tissue following NS oil administration for 21 days ( 35 ). Cuce et al also found a similar result as they reported a reduction in BAX and caspase 3 expression in the abdominal and thoracic aortic section, preventing apoptosis in the vessels of STZ-induced diabetic rats ( 57 ). The antiapoptotic effect of NS is not only beneficial for preventing cellular damage in DM but also resourceful in managing cancerous cells, as reported widely ( 86 ).…”
Section: Effect Of Ns On Dmmentioning
confidence: 52%
“…NS significantly increases the expression BCL2 in cardiac tissue following NS oil administration for 21 days ( 35 ). Cuce et al also found a similar result as they reported a reduction in BAX and caspase 3 expression in the abdominal and thoracic aortic section, preventing apoptosis in the vessels of STZ-induced diabetic rats ( 57 ). The antiapoptotic effect of NS is not only beneficial for preventing cellular damage in DM but also resourceful in managing cancerous cells, as reported widely ( 86 ).…”
Section: Effect Of Ns On Dmmentioning
confidence: 52%
“…In addition, NSO, the principal functional preparation of black cumin showed ameliorating effects in several STZ or alloxan-induced diabetic models. The major pharmacological mechanisms include the promotion of pro-survival and antiapoptotic signals [ 133 , 134 ], activation of growth factor signaling and inhibition of inflammatory response [ 135 ], increased insulin secretion and antioxidant molecules [ 136 ], suppression of extracellular matrix gene expression [ 137 ], and regulation lipid profiles [ 138 ]. Recently an in vitro cell-free assay reported alpha-amylase inhibitory activity of silver nanoparticles prepared from NSO, supporting its hypoglycemic effects [ 139 ].…”
Section: Benefits Of Black Cumin On Human Health and Disease Conditionsmentioning
confidence: 99%
“…Nigella sativa and isolated from black cumin seeds, thymoquinone has many beneficial effects such as being an antioxidant, antihyperlipidemic, antidiabetic, anti-inflammatory, gastroprotective and hepatoprotective. Researches on animals reveal that Thymoquinone has hypoglycemic, hypolipidemic and hypocholesterolemic effects [27][28][29] . Thymoquinone has been shown to regulate the production of antibodies.…”
Section: Thymoquinonementioning
confidence: 99%